Fitted Numerical Methods for Singular Perturbation Problems : Error Estimates in the Maximum Norm for Linear Problems in One and Two Dimensions (Revised Edition). - Miller, J. J. H. (World Scientific, 2012)
Since the first edition of this book, the literature on fitted mesh methods for singularly perturbed problems has expanded significantly. Over the intervening years, fitted meshes have been shown to be effective for an extensive set of singularly perturbed partial differential equations. In the revised version of this book, the reader will find an introduction to the basic theory associated with fitted numerical methods for singularly perturbed differential equations. Fitted mesh methods focus on the appropriate distribution of the mesh points for singularly perturbed problems. The global erro.